2008
DOI: 10.1002/nme.2317
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable postbuckling paths analyzed by means of the consistently linearized eigenproblem

Abstract: SUMMARYIn addition to the determination of load levels at critical points of stability problems, frequently the postbuckling behavior is of interest. For non-linear problems, the so-called consistently linearized eigenvalue problem is a suitable tangent linearization method, which facilitates determination of stability limits. The solution process of the eigenproblem is significantly simplified by appropriate coordinate transformations. Within this process, characteristic shapes of eigenvalue curves allow iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…For class I, (76) requires (Steinboeck et al 2008a) , 1 · . , d λ , and 4 λ ) as functions of κ which denotes the stiffness of an elastic spring attached to the structure, details of which will be given in Chapter 7 (Numerical investigation).…”
Section: Class Imentioning
confidence: 99%
See 3 more Smart Citations
“…For class I, (76) requires (Steinboeck et al 2008a) , 1 · . , d λ , and 4 λ ) as functions of κ which denotes the stiffness of an elastic spring attached to the structure, details of which will be given in Chapter 7 (Numerical investigation).…”
Section: Class Imentioning
confidence: 99%
“…6 shows a planar, static, conservative system with two degrees of freedom. The description of this system closely follows (Steinboeck et al 2008a) where additional details can be found. Both rigid bars, 1 and 2 have the same length L and in the non-buckled state they are in-line.…”
Section: Numerical Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…The other works were more focused on computational methods and issues, where geometrical imperfections of the uncertain nature are included (Papadopoulos et al [7]). Also, the very interesting and challenging problems of the post-buckling paths were analyzed (Steinböck et al [8]). However, determination of the higher probabilistic moments of both structural response and buckling modes is still very rare and the classical Monte-Carlo simulation is preferred.…”
Section: Introductionmentioning
confidence: 99%